Population Growth of the Generalist Mite Tyrophagus putrescentiae (Acari: Acaridida) Following Adaptation to High- or Low-Fat and High- or Low-Protein Diets and the Effect of Dietary Switch - Erban, Tomáš; Rybanská, Dagmar; Hubert, Jan (Environmental entomology, 2015)
Tyrophagus putrescentiae (Schrank, 1781) is a cosmopolitan generalist feeder that prefers foodstuffs of high-fat and high-protein content. Our aim was to investigate the population growth of T. putrescentiae after long-term nutritional adaptation to two distinct diets that are commonly infested in the synanthropic environment. Crushed dry dog food kernels provided a high-fat, high-protein, and low-carbohydrate diet, whereas wholemeal spelt flour provided a low-protein, low-fat, and high-carbohydrate diet. After >6 mo of nutritional adaptation, each of the two populations were used in two 28-d population growth tests: one that mites remained on their adaptation diet (homogenous diet treatment) and one that mites underwent a dietary switch (dietary switch treatment). Dietary treatment, nutritional adaptation, and their interaction all significantly influenced population growth. The homogenous diet treatment showed 7.5 times higher growth on the dog food diet than on flour. In the dietary switch, flour-adapted mites switching to dog food experienced five times greater population growth than the flour-adapted mites remained on flour, whereas the dog food-adapted population showed a 2.8-fold decrease in population growth when transferred to the flour. A comparison of means between the two dietary switch treatments showed a 1.9-fold higher population growth after flour-adapted mites were shifted to dog food than when the dog food-adapted mites were shifted to flour. We demonstrated that T. putrescentiae is able survive and reproduce for many generations on dry dog food and flour with different levels of success. High-fat and -protein food accelerated T. putrescentiae population growth compared with the high-carbohydrate diet.
Keywords: Population Growth; Animal Feed; krmivo pro zvířata; aklimatizace; dietní tuky; dietní proteiny; Acaridae; fyziologie výživy zvířat; populační růst; Animal Nutritional Physiological Phenomena; Animals; Dietary Proteins; Flour; mouka; Acclimatization; zvířata; Dietary Fats